PASAR MODAL SYARIAH SEBAGAI INSTRUMEN INVESTASI SYARIAH - Sumar’in Sumar’in (ADISAM PUBLISHER, 2023)
A country's economic development cannot be separated from good and appropriate investment. One effective form of investment is the capital market. The Islamic capital market is expected to be able to realize the main goal of Islamic finance in building economic growth while safeguarding social interests. The Islamic capital market has the benefit of mobilizing money flows from investors or the public to issuers listed on the market. Several criteria for establishing a sharia capital market are establishing fair prices, having perfect information, being free from usury, gharar, gambling and other transactions that conflict with sharia rules. Shares traded on the sharia capital market must come from issuers that meet sharia criteria and bonds issued must use mudarabah, musyarakah, ijarah, istisna' and salam.